That night on Thistle Lane [compact disc, unabridged] - Neggers, Carla (Neggers, Carla. Swift River Valley novel, 2013)
Working at the library, Phoebe O'Dunn sees a lot of stories. But she knows that in real life there is not always a happy ending. Things change when she discovers a room filled with old clothing, including a dress that is perfect for a gala in Boston. Disguised as a princess, she meets Noah Kendrick. Having wealth has made him suspicious of everyone, especially women. But this magical first encounter could lead to something more. And that comes in handy when a threat enters the picture.